The Casket of Medicine (Bhesajjamanjusa Chapters 1-18). Trans. Jinadasa Liyanaratne. - Norman, K. R. (Buddhist Studies Review, 2002)
The Casket of Medicine (Bhesajjamanjusa Chapters 1-18). Trans. Jinadasa Liyanaratne. Pali Text Society, Oxford 2002. xviii, 197 pp. £12.10. ISBN 0 86013 4003 2.